Methylene Blue Attenuates Significant Shifts in the Gut Microbiome Following Traumatic Brain Injury in Rodents. (1st September 2019) - McIntyre, Matthew; Burmeister, David M; Scroggins, Shannon; O'Boyle, Michael; Lai, Zhao; Schwacha, Martin; Watts, Lora; Nicholson, Susannah
Abstract: INTRODUCTION: Recent advances in DNA sequencing technology have elucidated the role that the gut microbiome (GM) plays in health and disease. There remains, however, a paucity of data on GM's role following a traumatic brain injury (TBI). While in Vivo studies have revealed neuroprotective effects of methylene blue (MB), we hypothesized that TBI would cause significant shifts in the GM that may be attenuated using MB. METHODS: Male rats underwent craniotomy and were randomized to sham (n = 6), mild TBI (1 mm; n = 10), or moderate (2 mm; n = 6) TBI induced via a pneumatic impactor, as previously described. Rats were also assigned to receive either 1 mg/kg MB or vehicle/no treatment (NT). Stool was collected for 16S rRNA sequencing preinjury, as well as 1, 3, and 7 d postinjury. Magnetic resonance imaging (MRI) was performed on a subset of animals in each group. Illumina MiSeq sequencing was performed, and MB analysis was conducted using the Qiime2 standard pipeline to determine the beta-diversity significance using PERMANOVA. RESULTS: In the absence of treatment, moderate (but not mild) TBI induced a significant shift in beta-diversity by day 3 ( P = .029), which became increasingly pronounced by day 7 ( P = .006). Treatment with MB reversed this shift, as these animals were not different from sham on day 7 ( P = .06). A significant increase in the phylum Bacteroidetes was noted after moderate TBI ( P = .009), which was attenuated with MB. Although alpha-diversity was not significantly altered after TBI, the MRI lesion volume positively correlated with Faith alpha-diversity (R2 = 0.82; P = .013). CONCLUSION: After moderate TBI, the GM represented a unique community compared to sham controls. The significant shift in GM beta-diversity was attenuated with the administration of MB in this in Vivo rodent model. This research may have clinical implications in the context of normalizing aberrations in the gut-brain axis following TBI.